PENINGKATAN KINERJA GURU : STRATEGI KEPALA MADRASAH DALAM MENINGKATKAN MUTU PENDIDIKAN - Abidah, Farah; Al-Maghfiroh, Fika; Putri, Dini Hilmiah; Hasanah, Nanda Maulidatul; Mubarokah, Laila; Banina, Nadhifa Najwa (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2025)
This study aims to analyze the strategies of madrasah principals in improving teacher quality as a key factor in achieving madrasah education quality. The background of this study is based on the importance of the role of teachers as the main implementers of the learning process, so that improving teacher quality is a strategic necessity in the development of educational institutions. This study uses a systematic literature review method by selecting various scientific sources, such as journal articles, books, and proceedings relevant to madrasah leadership and improving teacher professionalism. The analysis process was carried out through data reduction, theme grouping, and content synthesis to find patterns of effective leadership strategies. The results show that madrasah principals play an important role in improving teacher quality through three main strategies, namely needs-based professional development through training, academic supervision, and certification; strengthening teacher work behavior such as discipline, commitment, and teaching ethos; and creating a harmonious work environment through open communication, continuous motivation, and the proportional application of rewards and punishments. These three strategies have been proven to improve teachers’ pedagogical and professional competencies, improve the quality of learning, and encourage the achievement of optimal madrasah education quality. ABSTRAK Penelitian ini bertujuan untuk menganalisis strategi kepala madrasah dalam meningkatka mutu guru sebagai unsur utama dalam pencapaian mutu pendidikan madrasah. Latar belakang penelitian ini didasarkan pada pentingnya peran guru sebagai pelaksana utama proses pembelajaran, sehingga peningkatan mutu guru menjadi kebutuhan strategis dalam pengembangan lembaga pendidikan. Penelitian ini menggunakan metode systematic literature review dengan menyeleksi berbagai sumber ilmiah, seperti artikel jurnal, buku, dan prosiding yang relevan dengan kepemimpinan madrasah dan peningkatan profesionalisme guru. Proses analisis dilakukan melalui reduksi data, pengelompokan tema, serta sintesis isi untuk menemukan pola strategi kepemimpinan yang efektif. Hasil penelitian menunjukkan bahwa kepala madrasah berperan penting dalam meningkatkan mutu guru melalui tiga strategi utama, yaitu pembinaan profesional berbasis kebutuhan melalui pelatihan, supervisi akademik, dan sertifikasi; penguatan perilaku kerja guru seperti kedisiplinan, komitmen, dan etos mengajar; serta penciptaan lingkungan kerja harmonis melalui komunikasi terbuka, motivasi berkelanjutan, dan penerapan reward–punishment secara proporsional. Ketiga strategi tersebut terbukti mampu meningkatkan kompetensi pedagogik dan profesional guru, memperbaiki kualitas pembelajaran, serta mendorong tercapainya mutu pendidikan madrasah secara optimal.